Predicting the risk of postoperative liver failure and overall survival using liver and spleen stiffness measurements in patients with hepatocellular carcinoma. Issue 34 (August 2017) - Wu, Dongbo; Chen, Enqiang; Liang, Tao; Wang, Menglan; Chen, Bin; Lang, Bai; Tang, Hong
Abstract : Abstract: Postoperative liver failure (PLF) is the primary cause of morbidity and mortality after hepatic resection for hepatocellular carcinoma (HCC). In this study, we evaluated the efficacy of liver stiffness (LS) and spleen stiffness (SS), as measured by transient elastography (TE), for predicting the risk of PLF and overall survival (OS) in these patients. This prospective cohort study included 54 patients diagnosed with HCC who underwent hepatic resection between March 2013 and March 2014. Preoperative measurement of LS and SS using TE was performed on all patients underwent. The predictivity of LS and SS for PLF was assessed by receiver operating characteristic curve analysis. OS according to LS and SS was analyzed using the Kaplan–Meier method and compared using the log-rank test. PLF developed in seven (12.96%) patients. LS was significantly higher in patients with than in those without PLF ( P = .03). The area under the curve of LS for predicting PLF was 0.76 (95% confidence interval, 0.62–0.86; P = .02). However, there was no significant difference in SS between patients with and without PLF ( P = .36). Moreover, patients with an LS <16.2 kPa had significantly better OS than those with an LS ≥16.2 kPa ( P = .028). No significant difference in OS was observed between patients with an SS of <22.3 and ≥22.3 kPa ( P = .378). LS measured by TE can be used to predict the risk of PLF as well as OS in patients with HCC who have undergone hepatic resection. However, SS obtained using TE was not found to be a significant predictor for PLF and OS in our patients.